Relationship between emotional intelligence, self-esteem, and assertiveness among South Indian youth: A descriptive, cross-sectional study from Karnataka - Jagriti Niyogi; Renjulal Yesodharan; Rochelle Jane Dsa (Wolters Kluwer Medknow Publications, 2020)
Youth involves a lot of mental health issues. A descriptive cross-sectional study was undertaken to determine the relationship between emotional intelligence, self-esteem, and assertiveness among 432 youth (18-23 years) from selected colleges of Udupi district, Karnataka using Schutte Self-Report Emotional Intelligence Test, Rosenberg self-esteem scale, and Youth Assertiveness Scale. The mean emotional intelligence among youth was 124.99 ± 18.71, whereas the mean self-esteem and assertiveness scores were 18.48 ± 3.33 and 60.706 ± 7.077, respectively. Linear relationships among the key variables were assessed using the Karl Pearson's correlation coefficient. Self-esteem and assertiveness showed a weak positive relationship (r = 0.282 and 0.288, P = 0.001 respectively) with emotional intelligence, whereas the relationship between self-esteem and assertiveness also revealed a positive relationship (r = 0.367, P = 0.001). The significant correlation between these variables indicates a need for regular assessment among the youth. Rising self-esteem and training in assertiveness help the individual to use his emotions wisely and improve emotional intelligence.